FORMATION OF YOUTH POLICY IN THE CONDITIONS OF DEMOGRAPHIC CHALLENGES OF UKRAINE - Drapushko, Rostyslav; Gorinov, Pavlo; Filyk, Nataliia (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Objective: a comprehensive study of modern demographic processes and their impact on youth policy in modern Ukraine. Research methods: cognitive-analytical, sociological, statistical, comparative legal analysis and objective truth, etc. Results: generalized approaches to understanding the peculiarities of demographic policy and current trends in migration, identified areas of youth policy that meet existing challenges. Discussion: the tendencies and peculiarities of migration processes in the context of security challenges are clarified, the main directions of improving youth policy are generalized, the ways of improving the system of youth education are suggested. Today, Ukraine is at the center of global security and military challenges, among which demographic challenges are equally important. Most countries around the world are aware of the future demographic challenges of reducing the number of young people, and are therefore focusing their efforts on supporting programs that help support families with children. Ukraine needs a well-thought-out and clear strategy for the return of labor, where the main stimulus for return should be positive changes of economic, social and cultural nature in the homeland, which will include appropriate reforms. The basic stimulus for the return of Ukrainians is the appropriate economic preconditions, reforms that will enable them to implement the acquired knowledge and experience during their stay in other countries. A separate issue is qualitative changes in education. The state should also develop a clear and transparent and mutually beneficial policy to stimulate the development and promotion of entrepreneurship in Ukraine, be open to dialogue with small and medium-sized businesses, jointly develop programs for business development and culture of relations between the parties.